2015
DOI: 10.4187/respcare.04013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tidal Volume and Nebulizer Type and Position on Albuterol Delivery in a Pediatric Model of Mechanical Ventilation

Abstract: BACKGROUND: Optimization of factors affecting aerosol delivery during mechanical ventilation in the pediatric population is important. We hypothesized that increasing the tidal volume (V T ), using a vibrating mesh nebulizer, and placing the nebulizer at the ventilator would increase lung dose/delivery efficiency. METHODS: Continuous-output jet and vibrating mesh nebulizers loaded with albuterol (2.5 mg/3 mL) were compared when placed before the Y-piece and at the ventilator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 16 publications
5
39
1
1
Order By: Relevance
“…In contrast to findings in adult and pediatric models of conventional mechanical ventilation, [18][19][20][21] we found greater drug delivery with proximal placement of the VMN during infant conditions. The difference in findings can be explained in part by the circuit, VT, and breathing patterns used with different patient populations.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to findings in adult and pediatric models of conventional mechanical ventilation, [18][19][20][21] we found greater drug delivery with proximal placement of the VMN during infant conditions. The difference in findings can be explained in part by the circuit, VT, and breathing patterns used with different patient populations.…”
Section: Discussioncontrasting
confidence: 99%
“…Multiple investigators have described the impact of placement of a VMN in distal and proximal positions during simulated pediatric [19][20][21] and adult 18 mechanical ventilation. In an adult model without bias flow, Ari et al 18 reported twofold greater drug delivery with proximal versus distal position (prior to the humidifier).…”
Section: Discussionmentioning
confidence: 99%
“…While there are differences between the studies at each flow rate, the overall trends remain similar. Direct comparisons between inhaled dose are difficult due to several factors influencing the drug available for inhalation, such as the position of components in the ventilator circuit, simulated breathing settings and humidification affect the inhaled dose [37][38][39]. Golshahi et al [40] reported that increasing the tubing length from 20 cm to 50 cm increased the deposition fraction in the tube from 1.2% to 13.3%; this compared with a tube of length 1.8 m used in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found one exception that with gas flow at 5 L/min, inhaled dose was higher with continuous than inspiration synchronized aerosol, which might be explained by the significant reduction of the washing out effects due to the extremely low flow, resulting in reservoir of aerosol during exhalation for continuous aerosol. In contrast, because of the low flow rate to carry aerosol, aerosol generated at the inspiratory phase might not be able to fully reach the trachea yet before exhalation [20,21]. Due to the concerns of the aerosol waste during exhalation, continuous VMN was found to generate higher inhaled dose when placed at the inlet of humidifier, using the circuit and humidifier chamber as reservoir during exhalation.…”
Section: Comparison Of Inspiration Synchronized Vs Continuous Vmn Plamentioning
confidence: 99%